Peran Komando Kewilayahan Dalam Membantu Pemerintah Daerah Dan Implikasinya Terhadap Ketahanan Pangan (Studi Kampung Moibaken Dan Kampung Suneri Di Kabupaten Biak Numfor) - Zulkifli Mansyur (Universitas Gadjah Mada, 2022)
AbstractThis research was conducted in Biak Numfor Regency with the title Implementation of the role of regional command in assisting local governments and its implications for resilience with a focus on Moibaken and Suneri Villages, Biak Numfor Regency. The method used in this research is to use descriptive research with a qualitative approach that aims to describe and analyze the implementation of the role of the Regional Command in assisting local governments and its implications for food Resilience in Moibaken Village and Suneri Village, Biak Numfor Regency.observation), in-depth interviews, documentation,and library studies covering the role of regional commandos aimed at assisting local governments. The results of this study indicate that the implementation of the role of the Regional Command in assisting local governments and its implications for food Resilience has not run optimally. to farmers. as a regulator, a regulation is needed that regulates food Resilience. Then as a dynamist in its role it needs to be optimized by efforts to mobilize all existing units or form a post on food Resilience which is not just a guide as has been so far, so that with experience and togetherness the soldiers can take quick steps and actions to achieve food self-sufficiency. The strategies carried out by the Government and the Regional Command in Biak Numfor Regency in improving food Resilience are 1) socialization, this seems not yet optimal. 2) supervision and control, showing that the role of the Regional Command in supervision is good, but in controlling it is not optimal. 3) Education. shows that his role as an educator has not gone well because it is due to a lack of coordination with the government and farmers, 4) coordination, this shows that it is not optimal, this is due to a lack of communication made to farmers to increase awareness of the importance of food Resilience by paying attention to aspects of production agriculture, human resources, and agricultural innovation